Implicit measurement of the moral self-image using the Go/No-Go Association Task (GNAT): An empirical investigation of the convergent validity between explicit and implicit measures - Louisa Felicitas Bläßer (Junior Management Science (JUMS), 2025)
While people are increasingly aware of climate change, many still resist lifestyle changes. Research now focuses on understanding conscious (explicit) and unconscious (implicit) attitudes to encourage sustainable behavior. This thesis used the Go/No-Go Association Task (GNAT) to measure participants' implicit moral self-image and examine its correlation with an explicit moral self-image questionnaire, indicating convergent validity and effective application of the GNAT as an implicit measure of the moral self-image. After applying exclusion criteria, 68 participants were randomly assigned to two groups with different word lists. Results showed that repeated exposure to fewer words in group A led to little or no correlation, while group B, using more varied words, showed higher correlation and good convergent validity. This demonstrates that the GNAT effectively measures moral self-image when learning effects are avoided. The findings offer insights into implicit attitudes that influence decisions and yield practical implications for different stakeholders. This thesis contributes through its experimental design, adapted exclusion criteria, and sample correction of all perfect responses, validating the GNAT as an implicit measure and offering a foundation for future research.
Keywords: 650; convergent validity; explicit measures; go/no-go association task (GNAT); implicit measures; moral self-image